PERUBAHAN PERAN MAMAK TERHADAP KAMANAKAN DALAM KELUARGA BATIH DI KANAGARIAN BAYUA KECAMATAN TANJUNG RAYA KABUPATEN AGAM SUMATERA BARAT - Yuni Ariska; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Mamak's role in kamanakan is to guide and teach customs to kamanakan. Mamak acts as a leader for his kamanakan and kamanakan is a person led by mamak. The role of a mamak in Minangkabau is very much needed for a boy who will grow up. Mamak will give more guidance, religious teaching for children both boy about morals and especially supervise the behavior of children kamanakan. The role of mamak is considered to be both important and heavy, as the saying